Retention of nutrients, suspended particulate matter and phytoplankton in a pondage associated with a run‐of‐the‐river type hydroelectric power plant. Issue 2 (30th March 2015) - Sow, Mohamadou Mamoudou; Majdi, Nabil; Muylaert, Koenraad; Tackx, Micky; Julien, Frédéric; Probst, Jean‐Luc; Mialet, Benoît; Sutra, Carine; Probst, Anne; Thébault, Jean‐Marc; Kenarlikdjian, Mathilde; Gérino, Magali
Abstract: Reservoirs associated with run‐of‐the‐river type hydroelectrical power plants (i.e. pondages) have short water residence times. For this reason, pondages are thought to have a limited impact on the fluxes of particles and solutes transported by rivers. The Malause reservoir (South West France) is such a pondage. Fed by both the Garonne and Tarn rivers, it has a water residence time of only a few days. Incoming and outgoing fluxes of nutrients, suspended particulate matter (SPM) and phytoplankton were measured weekly over the course of 1 year. Mass balance calculations showed that Malause pondage retained 24% of soluble reactive phosphorus (SRP) supplied by both rivers on an annual basis. SRP retention occurred mostly in spring–summer, pointing to biological uptake. In addition, the pondage was a sink for SPM and phytoplankton, retaining 39% of SPM and 14% of chlorophyll a supplied by both rivers on an annual basis. The retention efficiency appeared to be constrained by water temperature and residence time. The pondage was a source of phytoplankton during summer, when temperature and water residence time was high. The pondage was a sink for SPM when water residence time was low (<1 day). Our observations highlight the need to reconsider the impact of minor hydrological discontinuities on the functioning of the river continuum. The shallow depth of the pondage and the presence of dense stands of submerged macrophytes have probably favoured the retention of nutrients and the sedimentation of particles within the pondage. Copyright © 2015 John Wiley & Sons, Ltd.